2017
DOI: 10.1186/s11658-017-0033-5
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-210 induces endothelial cell apoptosis by directly targeting PDK1 in the setting of atherosclerosis

Abstract: BackgroundAtherosclerosis is a chronically inflammatory disease and one of the leading causes of deaths worldwide. Endothelial cell apoptosis plays a crucial role in its development. Several microRNAs (miRNAs) are reportedly involved in atherosclerotic plaque formation, including miRNA-210 (miR-210). However, the underlying mechanism of its role in endothelial cell apoptosis during atherosclerosis is still largely unknown.MethodsA mouse model with atherosclerosis induced by a high-fat diet (HFD) was built in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 43 publications
0
62
0
Order By: Relevance
“…MicroRNA‐98 is able to rescue proliferation and relieve ox‐LDL‐triggered apoptosis of HUVECs by suppressing LOX‐1 (Chen, Liu et al, ). A novel role of miR‐210 has been uncovered in AS progression through regulating endothelial apoptosis (Li, Yang, Zhang, & Yang, ). Recently, miR‐182‐5p has demonstrated abnormal (Hirata et al, ; Hirata et al, ; Hirsch, Janovec, Stranska, & Bendriss‐Vermare, ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA‐98 is able to rescue proliferation and relieve ox‐LDL‐triggered apoptosis of HUVECs by suppressing LOX‐1 (Chen, Liu et al, ). A novel role of miR‐210 has been uncovered in AS progression through regulating endothelial apoptosis (Li, Yang, Zhang, & Yang, ). Recently, miR‐182‐5p has demonstrated abnormal (Hirata et al, ; Hirata et al, ; Hirsch, Janovec, Stranska, & Bendriss‐Vermare, ).…”
Section: Introductionmentioning
confidence: 99%
“…AS is an important cause of death and morbidity worldwide (23,24). Although miRNAs participate in ox-LDL-induced apoptosis of vascular endothelial cells (25), the detailed mechanism of miR-106b in AS is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier proliferation and apoptosis tests in BRL cells have revealed that cell proliferation is increased slowly and parts of cells undergo death after upregulation of rno-miR-210-3p [36]. This finding may be attributed to reduction of E2F3 and proteasome activity, which affects the cell cycle [37].…”
Section: Discussionmentioning
confidence: 99%